Minds in Chains: A Sociocybernetic Analysis of the Abrahamic Faiths - Scott, Bernard CE (Journal of Sociocybernetics, 2015)
I address the troubling matter of ‘pathological belief systems’, which I have previously defined as those that ‘restrict the right of actors to interact’. In particular, I consider the tangled ‘Gordian’ knot of beliefs that constitute the Abrahamic faiths: Judaism, Christianity and Islam. It is my belief that an analysis based on well-defined cybernetic principles can help cut through this knot and lay bare just what is pathological. The attraction of such an analysis is that it does not require one to pass judgements and ‘take sides’ with respect to the major controversies that divide the faiths. More generally, a properly formulated sociocybernetic analysis does not require one to pose any fundamental opposition between ‘science’ and ‘religion’. What the analysis does is help identify what are the key differences between ‘science’ and ‘religion’ as routes to knowledge and understanding, whilst noting that there are ‘undecidable questions’ about which an individual should be permitted to formulate her own beliefs without opposition or condemnation from others.